2013
DOI: 10.1002/er.3041
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluids with encapsulated tin nanoparticles for advanced heat transfer and thermal energy storage

Abstract: SUMMARY Novel high‐temperature heat transfer fluids (HTFs) with incorporated phase change nanomaterials were synthesized and tested for heat transfer and thermal energy storage. The advanced thermal properties were achieved by preparing a nanofluid consisting of core/shell silica encapsulated tin (Sn/SiO2) nanoparticles dispersed in a synthetic HTF Therminol 66 (TH66) at loadings up to 5 vol%. Tin nanoparticles were synthesized by modified polyole reduction method followed by sol–gel silica encapsulation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 33 publications
(37 reference statements)
0
64
0
Order By: Relevance
“…Transition SmA-I [33]. Series B: 4,4´´´-n-dialkyloxyquaterphenyls (n = 10, 11,12,15,14,15,16,17). Transition SmA-I.…”
Section: Liquid Crystals As Latent Heat Storage Materialsmentioning
confidence: 99%
“…Transition SmA-I [33]. Series B: 4,4´´´-n-dialkyloxyquaterphenyls (n = 10, 11,12,15,14,15,16,17). Transition SmA-I.…”
Section: Liquid Crystals As Latent Heat Storage Materialsmentioning
confidence: 99%
“…Recent studies [3] have shown that an enhancement in apparent specific heat is possible by introducing nanoparticles PCM in a base fluid. Unfortunately, an increase in viscosity occurs, leading to an extra pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts to improve these properties were mainly carried out on the rise in the thermal conductivity with the use of additives [1] or the introduction of solid microparticles or nanoparticles in a base fluid [2]. But the increase of the specific heat was also studied [3]. These engineered fluids are commonly named "nanofluids".…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the agglomeration of NPs cannot be disregarded, leading to poor suspension stability and high shear viscosity. In order to mitigate this unwanted effect alternative procedures based on the production of NPs directly into the fluids have been proposed (25)(26)(27)(28). Unfortunately, most of them (i.e., wet techniques) demonstrate low effectiveness to avoid the NPs agglomeration and/or show pollution problems due to the surfactants used in the synthesis of NPs.…”
Section: Introductionmentioning
confidence: 99%